THE STRUGGLE OF WOMEN EXISTENCE IN “ISN’T IT ROMANTIC” NOVEL BY WENDY WESSERSTEIN - Devi Cintia Kasimbara (eScience Humanity Journal, 2021)
This study aimed to reveal the struggle of women to gain existence in the novel as a representation of social phenomena. The data source of this research was Isn't It Romantic drama by Wendy Wesserstein. This novel is about women who want to achieve their dreams without the participation of their parents. They want to live without any interference from their parents. To reveal the struggle for existence, the researcher uses the existentialism approach by Simone Beauvoir. Existentialists fight for the nature of human existence, especially for women who have been subordinated to the patriarchal system. The method used in this research is Descriptive qualitative method. The close reading data collection method is effective in tracing data relevant to research variables. The analysis method is carried out critically by using an existentialism approach. The researcher got three main analyses toward the novel, they are: independence over women, authority in making decisions, and lastly, the same existence as a human being.